ASSESSMENT OF HUMANISTIC PRINCIPLES OF ECOTOURISM IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The negative impact of tourism on the environment is a consequence of the ecology of human (individual) and society. The application of humanistic principles will give a positive solution to the ecology of human and society, which in turn will create a tourism–eco-tourism–sustainable tourism system. In the article it is shown that this system will contribute conditions for society sustainable development.
Keywords: tourism; ecology; sustainable development; society